Modeling of processes of friction and wear in tribosystems in the conditions boundary lubrication. Part 3. The quality factor of tribosystem - Войтов, В.А.; Захарченко, М.Б. (Problems of Tribology, 2016)
A mathematical model for calculating the wear rate and friction coefficient tribosystems operating under boundary lubri-cation, which allows you to define resource and mechanical friction losses projected tribosystems without prior experiment was de-veloped. The model takes into account the property of the material compatibility in tribosystem which received definition as Q-factor tribosystem. The results of modeling the wear rate and friction coefficient of various designs tribosystems with the assessment of the adequacy and modeling errors are shown.